2016
DOI: 10.1302/0301-620x.98b8.37623
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and impact of sarcopenia on degenerative lumbar spinal stenosis

Abstract: This study demonstrated a higher prevalence of sarcopenia in patients with DLSS and highlighted its negative effect on clinical outcomes. Cite this article: Bone Joint J 2016;98-B:1093-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 21 publications
0
36
1
Order By: Relevance
“…A retrospective study demonstrated that the prevalence of sarcopenia, as defined by hand grip strength, in populations with degenerative spinal canal stenosis, was 24%, while it was 12% in control populations in Korea [ 20 ]. While a previous study of sarcopenia prevalence in lumbar spinal stenosis defined sarcopenia based on hand grip strength and skeletal muscle mass measured by bioelectric impedance (BIA) [ 20 ], DXA was applied in this study instead. Though the results of BIA have been shown to correlate with DXA, BIA results were confounded by fluid retention [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study demonstrated that the prevalence of sarcopenia, as defined by hand grip strength, in populations with degenerative spinal canal stenosis, was 24%, while it was 12% in control populations in Korea [ 20 ]. While a previous study of sarcopenia prevalence in lumbar spinal stenosis defined sarcopenia based on hand grip strength and skeletal muscle mass measured by bioelectric impedance (BIA) [ 20 ], DXA was applied in this study instead. Though the results of BIA have been shown to correlate with DXA, BIA results were confounded by fluid retention [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…LBP is one of the most common symptoms treated in daily medical practice. Park et al investigated the prevalence of sarcopenia and lumbar spinal stenosis in Korea [ 16 ]. The prevalence of sarcopenia was higher in people with lumbar spinal stenosis than in normal people.…”
Section: Discussionmentioning
confidence: 99%
“…This propensity score-matched case-control study was performed within the framework of a prospective study designed to develop criterion-referenced health-related fitness standards for the National Fitness Award. 7 This study was approved by the Institutional Review Boards of Seoul National University Bundang Hospital and Korea Institute of Sport Science, and was conducted in accordance with the approved study protocol (IRB No. B-1612-373-301).…”
Section: Methodsmentioning
confidence: 99%